2019
DOI: 10.2147/cmar.s218532
|View full text |Cite
|
Sign up to set email alerts
|

<p>Serum Dickopff 1 as a Novel Biomarker in Hepatocellular Carcinoma Diagnosis and Follow Up After Ablative Therapy</p>

Abstract: Background: This study aimed to evaluate the role of Dickopff 1 (DKK1) serum levels as a marker for early detection of hepatocellular carcinoma (HCC) and to compare it with alphafetoprotein (AFP) after non-surgical intervention (microwave ablation, radiofrequency ablation) in HCC. Patients and methods: This prospective study was conducted in Al-Mahalla hepatology teaching hospital from June 2015 to June 2017. One hundred and twenty patients were included. They were classified into four groups: Group A: 40 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
(31 reference statements)
1
3
0
Order By: Relevance
“…On comparing the four studied groups as regard the alphafetoprotein (AFP), its level was significantly higher in group I than group II, III and IV which showed that AFP level can distinguish HCC cases from cirrhosis cases, HCC cases from chronic viral hepatitis without cirrhosis cases and HCC cases from controls. This result agreed with Erdal et al, (2016) and Younis et al, (2019) who showed that AFP level can distinguish HCC cases from cirrhosis cases, and HCC cases from controls [37][38] . There was a significant correlation between smoking and serum level of DKK1which agreed with Jorde et al, (2019) who concluded that smokers had significantly higher DKK1 than non-smokers [39] .…”
Section: Discussionsupporting
confidence: 91%
“…On comparing the four studied groups as regard the alphafetoprotein (AFP), its level was significantly higher in group I than group II, III and IV which showed that AFP level can distinguish HCC cases from cirrhosis cases, HCC cases from chronic viral hepatitis without cirrhosis cases and HCC cases from controls. This result agreed with Erdal et al, (2016) and Younis et al, (2019) who showed that AFP level can distinguish HCC cases from cirrhosis cases, and HCC cases from controls [37][38] . There was a significant correlation between smoking and serum level of DKK1which agreed with Jorde et al, (2019) who concluded that smokers had significantly higher DKK1 than non-smokers [39] .…”
Section: Discussionsupporting
confidence: 91%
“…The glycoprotein Dickkopf-1 (DKK-1), expressed mainly in the placenta and embryonic tissues, is an antagonist of the Wnt/β-catenin signaling pathway and is elevated in several cancer types. DKK-1 shows higher efficacy for detecting HCC than AFP in phase 4 trials ( 206 208 ), but midkine is more precise than DKK-1 in cirrhotic HCV patients ( 209 ). A combination of Golgi protein 73, AFP, and Dickkopf-1 increases the sensitivity and specificity of HCC detection ( 210 ).…”
Section: Promising New Biomarkers For Clinical Applicationmentioning
confidence: 99%
“…DKK-1 expression has also been reported to be elevated in HCC tissues [ 20 ], and DKK-1 is dysregulated in various other malignant tumors, such as pancreatic cancer, colorectal cancer, multiple myeloma, and chronic lymphocytic leukemia [ 21 , 22 , 23 , 24 ]. The diagnostic value of serum DKK-1 levels for HCC has previously been determined [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. However, although DKK-1 expression is activated in HpSC-HCC with the activation of Wnt signaling, DKK-1 itself is known to inhibit the Wnt signaling pathway, and the role of DKK-1 expression in the process of HpSC-HCC development remains elusive.…”
Section: Introductionmentioning
confidence: 99%